THE ROLE OF MEDIA LITERACY OF YOUNG ATHLETES IN THE PROCESS OF FORMATION OF THEIR VALUE SYSTEM - Skok N.S.; Baryaev A.A.; Kulikov V.S.; Ulitskaya T.I. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to study the level of media competence indicators of athletes from the sports reserve (hereinafter referred to as athletes) with signs of deviant behavior in the context of the formation of value orientations. Methods and structure of the study. An analysis of literary sources on the criteria of media competence was carried out, a survey, observation, and a pedagogical experiment were conducted. The parameters and indicators of media competence (Fedorov A.V.) were selected, according to which a questionnaire survey of athletes was conducted (2023-2024). The results of pedagogical observation in the process of educational activities to form value orientations were analyzed and summarized. A correlation analysis was performed between the level of motivational indicators of media competence and value orientations of athletes (n=14, by sports: orienteering, handball, volleyball, rowing and sailing, age 16-17 years). Results and conclusions. The levels of motivational indicator of media competence of athletes were established. A survey was conducted at the beginning and at the end of the pedagogical experiment. The motives and genre preferences for consuming media content were studied: for self-affirmation and gaining knowledge about life outside the sports environment; the desire to learn to distinguish false (negative propaganda) information from truthful information; interest in the media space in the communication of athletes and youth artistic groups. The results of the study revealed an overestimation of the athletes’ capabilities in interpreting content.